The Role of Foreign Currency Debt in Public Debt Management. (IMF Working Papers; Working Paper ;, 1995)
This paper analyzes the choice between public debt denominated in domestic currency and foreign currency in the context of public debt management theories. It discusses the experience of Belgium, Denmark, Ireland, Italy, New Zealand and Sweden and relates it to the theoretical arguments in favor or against the Issuance of foreign currency debt.